Africa agriculture trade monitor 2022 - Bouët, Antoine; Odjo, Sunday P.; Zaki, Chahir (AKADEMIYA2063, 2022)
The 2022 Africa Agriculture Trade Monitor, a flagship publication of AKADEMIYA2063 and the International Food Policy Research Institute, provides an overview of trade in agriculture in Africa, including analysis of short- and long-term trends and drivers behind Africa’s global trade, intra-African trade, and trade within Africa’s regional economic communities. The 2022 report looks at the impact of the Russia-Ukraine war; Africa’s participation in global value chains; intraregional trade in processed agricultural products; the potential benefits of ambitious implementation of the African Continental Free Trade Area Agreement, and includes focused chapters on value chains for cocoa, coffee, and tea and on trade integration in Economic Community of Central African States.